2016
DOI: 10.1073/pnas.1607850113
|View full text |Cite
|
Sign up to set email alerts
|

Direct calorimetric verification of thermodynamic instability of lead halide hybrid perovskites

Abstract: Hybrid perovskites, especially methylammonium lead iodide (MAPbI 3 ), exhibit excellent solar power conversion efficiencies. However, their application is plagued by poor chemical and structural stability. Using direct calorimetric measurement of heats of formation, MAPbI 3 is shown to be thermodynamically unstable with respect to decomposition to lead iodide and methylammonium iodide, even in the absence of ambient air or light or heat-induced defects, thus limiting its long-term use in devices. The formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
278
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(304 citation statements)
references
References 35 publications
24
278
1
1
Order By: Relevance
“…[266] Despite the differences between these studies, all report that MAPbI 3 was found to be the least stable, while MAPbCl 3 is the most stable. Partially substituting the iodide with bromide or chloride would, therefore, be expected to improve the thermodynamic stability of the perovskite compared to the pure iodide material, while maintaining the good photovoltaic performance.…”
Section: Mixed-halide Mixed-cation Perovskitesmentioning
confidence: 89%
“…[266] Despite the differences between these studies, all report that MAPbI 3 was found to be the least stable, while MAPbCl 3 is the most stable. Partially substituting the iodide with bromide or chloride would, therefore, be expected to improve the thermodynamic stability of the perovskite compared to the pure iodide material, while maintaining the good photovoltaic performance.…”
Section: Mixed-halide Mixed-cation Perovskitesmentioning
confidence: 89%
“…Using direct calorimetric techniques, Navrotsky et al 37 have shown MAPI to be thermodynamically unstable with respect to decomposition to PbI 2 and MAI. Here, the same intrinsic decomposition reaction was investigated involving the formation of PbI 2 and organic iodides as well as decomposition to the d-phase:…”
Section: -36mentioning
confidence: 99%
“…The lattice energies of CH 3 20 . Lattice energies of the corresponding inorganic perovskites (CsPbI 3 , CsPbBr 3 and CsPbCl 3 ) are very similar to their organic counterparts.…”
Section: B Stability Analysis Of Hybrid Organic Halide Perovksitesmentioning
confidence: 99%